Measurement of four-jet differential cross sections in √s = 8 TeV proton-proton collisions using the ATLAS detector - Alconada Verzini, María Josefina (2015)
Differential cross sections for the production of at least four jets have been measured in proton-proton collisions at √s = 8 TeV at the Large Hadron Collider using the ATLAS detector. Events are selected if the four anti-kt R = 0.4 jets with the largest transverse momentum (pT) within the rapidity range |y| < 2.8 are well separated (ΔRmin4j > 0.65), all have pT > 64 GeV, and include at least one jet with pT > 100 GeV. The dataset corresponds to an integrated luminosity of 20.3 fb-1. The cross sections, corrected for detector effects, are compared to leading-order and next-to-leading-order calculations as a function of the jet momenta, invariant masses, minimum and maximum opening angles and other kinematic variables.